Distinctive speech signature in cerebellar and parkinsonian subtypes of multiple system atrophy - Rusz, Jan; Tykalová, Tereza; Salerno, Giulio; Bancone, Serena; Scarpelli, Johara; Pellecchia, Maria Teresa (Journal of neurology, 2019)
Although motor speech disorders represent an early and prominent clinical feature of multiple system atrophy (MSA), the potential usefulness of speech assessment as a diagnostic tool has not yet been explored. This cross-sectional study aimed to provide a comprehensive, objective description of motor speech function in the parkinsonian (MSA-P) and cerebellar (MSA-C) variants of MSA. Speech samples were acquired from 80 participants including 18 MSA-P, 22 MSA-C, 20 Parkinson's disease (PD), and 20 healthy controls. The accurate differential diagnosis of dysarthria subtypes was based on quantitative acoustic analysis of 14 speech dimensions. A mixed type of dysarthria involving hypokinetic, ataxic and spastic components was found in the majority of MSA patients independent of phenotype. MSA-P showed significantly greater speech impairment than PD, and predominantly exhibited harsh voice, imprecise consonants, articulatory decay, monopitch, excess pitch fluctuation and pitch breaks. MSA-C was dominated by prolonged phonemes, audible inspirations and voice stoppages. Inappropriate silences, irregular motion rates and overall slowness of speech were present in both MSA phenotypes. Speech features allowed discrimination between MSA-P and PD as well as between both MSA phenotypes with an area under curve up to 0.86. Hypokinetic, ataxic and spastic dysarthria components in MSA were correlated to the clinical evaluation of rigidity, cerebellar and bulbar/pseudobulbar manifestations, respectively. Distinctive speech alterations reflect underlying pathophysiology in MSA. Objective speech assessment may provide an inexpensive and widely applicable screening instrument for differentiation of MSA and PD from controls and among subtypes of MSA.
Keywords: nemoci mozečku; Female; Multiple System Atrophy; dysartrie; ženské pohlaví; průřezové studie; lidé; Parkinsonian Disorders; Speech Acoustics; kohortové studie; Cerebellar Diseases; Cohort Studies; Cross-Sectional Studies; Male; Aged; parkinsonské poruchy; akustika řeči; lidé středního věku; multisystémová atrofie; senioři; mužské pohlaví; Dysarthria; Middle Aged; Humans